# Question #07f4e

##### 2 Answers
Nov 14, 2017

$- 12 , - 13 , - 14$

#### Explanation:

$\left(- 12\right) + \left(- 13\right) + \left(- 14\right) = - 39$
You know you need 3 integers that all have about the same value because they are consecutive, so divide 39 by 3.
$\frac{39}{3} = 13$
You can then use 2 integers, one greater and one less than -13, to reach -39

Nov 14, 2017

$- 12 , - 13 , - 14$

#### Explanation:

Given: three consecutive integers with sum of -39

We know that the integers are consecutive, so let
$x - 1 = 1 \text{st integer}$
$x = 2 \text{nd integer}$
$x + 1 = 3 \text{rd integer}$

Since we know that the sum of the three integers is -39, we know that
$\left(x - 1\right) + \left(x\right) + \left(x + 1\right) = - 39$

Solving for this:
$\left(x - 1\right) + \left(x\right) + \left(x + 1\right) = - 39$
$x - 1 + x + x + 1 = - 39$
$3 x = - 39$
$x = - 13$

In this case, by substituting the computed $x$ with the values above, we would know that:
1st integer = -14
2nd integer = -13
3rd integer = -12

*Note that it does not matter if you add positive 1 or negative 1 just as long as you use consistent terms and you define your variables properly. So regardless of whether you use x, x - 1, x - 2 to define your three integers or x, x + 1, x + 2, you will still arrive at the same answer.